Economic growth and financial depth: Is the relationship extinct already? - Peter L. Rousseau; Paul Wachtel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Although the finance–growth nexus has become firmly entrenched in the empirical literature, studies that question the strength of the empirical results have appeared and seem to have become more frequent as well. In this paper we re-examine the core crosscountry panel results that established the relationship between financial depth and growth rates. We examine the sensitivity of the core result to changes in time period and variation in the sample of countries included. We find that the finance–growth relationship in not as strong with more recent data as it was in the original studies with data for the period from 1960 to 1989. We offer two possible explanations. First, financial depth may have had greater value as a shock absorber in the 1970s and 1980s, decades characterized by worldwide nominal shocks Second, the spread of financial liberalization in the 1980s may have led to increasing financial depth in countries that lacked the legal or regulatory infrastructure to successfully exploit financial development.
Keywords: E44; G10; O40; 330; finance–growth nexus; rolling regression; robustness; cross-country growth; Wirtschaftswachstum; Finanzsektor; Welt